Development of Teaching Materials Handout Material KH. Ahmad Rifa'i in Learning the History of the Indonesian Independence Struggle at SMA Negeri 1 Bandar - Jantari, Karina Hasbi; Bain, Bain; Romadi, Romadi (Universitas Negeri Semarang, 2022)
This study aimed to analyze the historical teaching materials needed in 1 Bandar High School to develop teaching materials in KH. Ahmad Rifa'i, and the feasibility of KH handout material. Ahmad Rifa'i. The method used in this study is research and development with development models developed by Thiagarajan, Semmel, and Semmel. This research goes through four steps: defining, planning, developing, and disseminating. The study results show that (1) Learning history in SMA 1 Bandar has used teaching materials consisting of LKS and modules available at school. Teaching materials regarding KH still need to be added to the material. Ahmad Rifa'i. Requires teaching material about the material; (2) Development has been carried out with four steps, namely defining, designing, developing, and implementing; (3) Based on the level of feasibility of the results of the validation of material experts and media experts, the developed handouts showed 82.4% for material validation and 83.1% for media validation. In addition, the results of the teacher's response were 87.2%, and the results of the students' response were 96.7%. Learning to obtain teaching materials is worth using in history learning at school.